Dupilumab normalizes correlates of lysosomal function in atopic dermatitis - Christina Bürgler; Danielle Dutoit; Susanne Radonjic‐Hoesli; Kathrin Thormann; Mathias Lehmann; Shida Yousefi; Hans‐Uwe Simon; Dagmar Simon (Wiley, 2024)
Abstract Background Atopic dermatitis (AD) is characterized by skin barrier dysfunction and immune dysregulation. Autophagy, which is important for the epidermal differentiation, is impaired in AD. The treatment with dupilumab, an interleukin (IL)‐4/IL‐13 receptor blocker, has been shown to reduce skin inflammation and restore the skin barrier. Objectives This study aimed to investigate the effect of dupilumab on the expression of key proteins involved in autophagy and lysosomal degradation. Methods We performed immunofluorescence staining and microscopic analyses of skin specimens of AD patients, taken before and under (6-10 weeks) therapy with dupilumab, to investigate the expression of autophagy‐related (ATG) 5 and ATG7 proteins, beclin‐1, microtubule‐associated protein light chain 3 (LC3B), sequestosome‐1 (p62), lysosomal proteases (cathepsins B, D and L), serine protease inhibitors (SERPINB3, SERPINB4) as well as IL‐33 and thymic stromal lymphopoietin (TSLP). Results The expression of LC3B and p62 as well as SERPINB3 and SERPINB4 was highly increased in untreated AD skin compared to non‐lesional skin and normal skin and decreased upon dupilumab therapy. In contrast, the AD‐associated increased expression of both ATG5 and ATG7 further increased under therapy. Before therapy, cathepsin D and L expression levels were significantly lower compared to normal skin, but increased following the initiation of dupilumab therapy. The increased expression of IL‐33 and TSLP in the epidermis of AD patients correlated with that of LC3B and p62. Conclusions Our study provides further evidence that autophagy is inhibited in lesional AD skin owing to lysosomal dysfunction. Upon dupilumab therapy, a restoration of dysregulated key players of autophagy is observed.